Choroidal vascularity index in health and systemic diseases: a systematic review - Mehrdad Motamed Shariati; Sahel Khazaei; Mariye Yaghoobi (International Journal of Retina and Vitreous)
Abstract Background The choroid, a highly vascular structure within the eye, is significantly influenced by various systemic conditions. The advent of enhanced depth optical coherence tomography has improved our ability to evaluate choroidal pathophysiology. The choroidal vascularity index (CVI), a noninvasive and reliable tool, serves as an effective means of assessing the choroidal vascular structure. Recent studies have increasingly focused on exploring CVI alterations under different systemic conditions. This study aims to provide a comprehensive summary of the latest research findings in this area. Methods A systematic literature review was conducted on October 1, 2023, using two databases, MEDLINE (via PubMed) and Scopus. Search terms were tailored specifically for each database to ensure a thorough exploration of relevant literature. The studies identified were qualitatively assessed, with particular emphasis on outcomes related to CVI and choroidal thickness. Results A total of 48 studies were included in the review, encompassing a diverse range of systemic conditions such as diabetes, central nervous system disorders, cardiovascular diseases, autoimmune disorders, and infectious diseases. Notable reductions in CVI were observed in diabetic retinopathy, autoimmune diseases, and neurodegenerative disorders. Additionally, the review highlighted variations in CVI values related to the severity of systemic diseases, indicating its potential use as a biomarker for disease progression. Conclusion This review highlights the significant correlation between variations in the choroidal vascularity index and diverse systemic conditions affecting hemodynamics. An enhanced understanding of CVI provides deeper insights into the pathophysiological mechanisms underlying these disorders and positions CVI as a promising biomarker for early detection and monitoring. Nevertheless, its clinical utility warrants careful assessment. Future research should address the potential limitations of CVI to fully capitalize on its diagnostic and prognostic potential.